2022
DOI: 10.24251/hicss.2022.354
|View full text |Cite
|
Sign up to set email alerts
|

Educative Sensemaking on Social Media: An Empirical Investigation of Informal Learning on YouTube

Abstract: Educational videos on social media are widely used in informal learning. However, empirical studies hardly look into sensemaking, a key aspect in the construction of meaning and knowledge, of educational videos on social media in informal learning, despite the growing interest and practice in educative sensemaking. This study addresses this research gap. We draw upon sensemaking theories and investigate how the physical properties of educational videos affect sensemaking. Our research shows how information con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Finally, a weighted average of the values was calculated, with 1/3 weighting on the percentage of likes, and 2/3 weighting on the percentage of views, as shown in Eq. (1).…”
Section: Recommendation System Algorithm and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a weighted average of the values was calculated, with 1/3 weighting on the percentage of likes, and 2/3 weighting on the percentage of views, as shown in Eq. (1).…”
Section: Recommendation System Algorithm and Resultsmentioning
confidence: 99%
“…The increasing amount of data, and the growing use of the Internet have given rise to a new form of learning: informal education [1].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microlearning has been used for learning language (Dingler et al, 2017;Inie and Lungu, 2021), programming skills (Aitchanov et al, 2013;Skalka and Drlık, 2017), and in many other fields. Online communities are highly conducive to informal learning, because they afford users asking and answering questions (Kumar and Gruzd, 2019), resource sharing (Esteve Del Valle et al, 2017), users consuming information at their own pace (Shen et al, 2022), users finding mentors with different levels of expertise (Campbell et al, 2016), among many other things. Though a majority of studies surrounding informal learning in online communities focuses on text-based communities such as Reddit or Twitter, recent research into video-based communities like YouTube (Shen et al, 2022;Tan, 2013;Vizcaıno-Verdú et al, 2019) has shown that such platforms also afford informal learning in similar ways as their text-based counterparts.…”
Section: Informal Learning In Online Communitiesmentioning
confidence: 99%
“…Online communities are highly conducive to informal learning, because they afford users asking and answering questions (Kumar and Gruzd, 2019), resource sharing (Esteve Del Valle et al, 2017), users consuming information at their own pace (Shen et al, 2022), users finding mentors with different levels of expertise (Campbell et al, 2016), among many other things. Though a majority of studies surrounding informal learning in online communities focuses on text-based communities such as Reddit or Twitter, recent research into video-based communities like YouTube (Shen et al, 2022;Tan, 2013;Vizcaıno-Verdú et al, 2019) has shown that such platforms also afford informal learning in similar ways as their text-based counterparts. This present study intends to add to the scholarship on informal learning on video-based online communities by studying TikTok, a platform that has not been extensively studied so far in this context.…”
Section: Informal Learning In Online Communitiesmentioning
confidence: 99%
“…Prosumer performance in the perspective of media and communication studies pays excellent attention to aspects of narrative and aesthetic skills because the learning community believes in the power of narrative and expanding dialogue [73]. Therefore, the context of informal learning platform as an independent education model that supports hybrid formal education on YouTube requires several continuous activities [74][75][76], such as 1) interpret, recognize, and describe such genres in diff erent media and platforms. 2) Compare, highlighting the diff erences and similarities between diff erent narrative worlds.…”
Section: Prosumers In Hybrid-education Modelmentioning
confidence: 99%